Development of Elastomeric Rubber Bearing Utilizing Core-and-Filler System. (March 2022) - Tan, Kar Chun; Hejazi, Farzad; Mohammadi Esfahani, Hojjat; Chong, Thomas
Abstract: Elastomeric bearing is the most common base isolation system for structures and bridges to dissipate effect of applied vibration and ground motion. To improve performance of the base isolators, lead core is implemented in the rubber bearings and it successfully enhances the damping and stiffness of elastomeric bearing. However, the most notable disadvantage of lead-core rubber bearing is the lead toxicity impact on extensive environmental contamination, which restrained application of lead in construction industry. Therefore, in the present study, an attempt has been made to develop a new elastomeric laminated bearing utilizing core-and-filler system instead of lead core to improve the performance of bearing. Two types of filler, namely granular and shape memory polymer are implemented. Granular filler is prepared by using silica sand, while shape memory polymer filler is prepared by using epoxy resin. Also, steel core is implemented to improve the stiffness of filler. The performance of proposed bearing utilizing with core-and-filler system is evaluated using finite element simulation. The numerical results revealed the efficiency of bearing with proposed system by providing considerable damping and stiffness. The replacement of lead core with fully filled granular and shape memory polymer showed improvement in terms of stiffness, and this proved core-and-filler system is effective in limiting lateral displacement. Also, the prototype of base isolation devices with both granular and shape memory polymer fillers are fabricated and tested via cyclic shear test. The results are compared with finite element analysis results, and good agreement between experimental tests results and numerical simulation response is shown. The experimental testing results proved that implementation of core-and-filler system improves the lateral resistance of proposed elastomeric bearing. In overall, it can be concluded that the implementation of core-and-filler system provides a reliable improvement to the performance of conventional elastomeric bearing and can be considered as alternative system to lead core rubber bearings.